From trustworthy AI to technical standards : The distinctive European approach to artificial intelligence regulation - Gornet, Mélanie (Institut polytechnique de Paris, 2025)
L'Europe a été à l'avant-garde de l'éthique de l'intelligence artificielle (IA), en élaborant des chartes et des principes non contraignants sur l'IA « digne de confiance ». Le terme « digne de confiance » est utilisé par l'Europe pour désigner les systèmes d'IA qui sont « éthiques », « légaux » et « techniquement robustes ». L'Europe a complété ces principes non contraignants par un texte de loi sur l'IA, connu sous le nom de règlement sur l'IA, ou AI Act. Le règlement sur l'IA est l'un des premiers cadres légaux au monde à réglementer les systèmes d'IA dans différents secteurs et cas d'utilisation, en mettant l'accent sur la sécurité et la protection des droits fondamentaux. Pour les questions opérationnelles, le règlement sur l'IA s'appuie principalement sur des normes techniques en cours d'élaboration. L'approche européenne combine donc trois niveaux d'instruments réglementaires : les chartes éthiques de l'IA, le règlement sur l'IA et les normes techniques.L'approche par la normalisation est traditionnelle dans le domaine de la sécurité des produits, mais dans le règlement sur l'IA, les normes sont également censées répondre aux préoccupations en matière de droits fondamentaux. Pour éviter de faire des choix normatifs difficiles, les organismes de normalisation jouent la carte de la sécurité en élaborant des normes qui restent à un niveau élevé. De plus, dans le cadre du règlement sur l'IA, la responsabilité de l'élaboration des normes techniques est déléguée à des organismes de normalisation privés, où les grandes entreprises multinationales sont surreprésentées et exercent une influence considérable. Ces normes sont également généralement payantes, bien que la situation puisse évoluer dans les années à venir après une récente jurisprudence de la Cour de justice de l'Union européenne. Les experts en normalisation sont donc sous pression pour fournir des normes à temps et de bonne qualité. Europe has been at the forefront of Artificial Intelligence (AI) ethics, developing non-binding charters and principles on "trustworthy'' AI. The term "trustworthiness'' is used by Europe to designate AI systems that are "ethical'', "legal'' and "technically robust''. Europe has supplemented these non-binding principles with a binding regulation on AI, known as the AI Act. The AI Act is one of the world's first comprehensive frameworks for regulating AI systems across different industries and use cases, focusing on safety and protection of fundamental rights. The AI Act relies, for operational questions, mostly on technical standards that are in the course of development. The European approach thus combines three layers of regulatory instruments: AI ethics charters, the AI Act and technical standards.The standardisation approach is traditional in product safety, but under the AI Act, standards are also expected to address fundamental rights concerns. To avoid making hard normative choices, standardisation organisations are playing it safe, developing standards which remain at a high-level. Moreover, under the AI Act, the responsibility for developing technical standards is delegated to private standardisation bodies, where large multinational companies are over-represented and hold significant influence. These standards are also often locked behind paywalls, although the situation may evolve in the coming years after a recent case law from the Court of Justice of the European Union. Standardisation experts therefore face pressures to deliver standards on time and of good quality.
Keywords: AI Act; Apprentissage machine; Artificial Intelligence; Ethics; Inteligência artificial; Intelligence Artificielle; Intelligence artificielle; Machine learning; Normes techniques; Regulation; Règlement IA; Régulation; Technical standards; Éthique

The Protection of E-Banking Services Against Cybercrimes in Cameroon: Prospects and Challenges - Ghaseh, Nkambeh Allen (International Multilingual Journal of Science and Technology, 2025)
This article seeks to examine the extent to which users of e-banking services are protected in Cameroon. Over the past decades financial transactions have gradually emerged from traditional methods to modern forms of banking. The Information and Communication Technology (ICT) has transformed the banking system into a digital arena. With e-banking, customers can access their bank accounts, transfer funds, pay bills, and check their accounts balances. Banks serve as the backbone of every modern economy and should be protected. The development of e-banking in the 1980s with the aid of ICT has rendered banks and their customers vulnerable to cybercrimes. As an effort to combat cybercrimes and ensure cyber security in Cameroon, the 2010 Cyber Law provides both substantive and procedural rules. It is rather unfortunate that, the measures put in place to ensure cyber security and protect bank customers against cybercrimes are to a greater extent ineffective. The main objective of this article is to determine the protection accorded to banks and their customers against cybercrimes. The method adopted in the course of this work is doctrinal wherein, both primary and secondary sources of data were collected. The findings reveal among others that, the measures put in place to combat cybercrimes within the banking sphere in Cameroon are not effective. There is lack of explicit definitions for cyber offences. Most of the offences provided by the 2010 Cyber Law are vague and ambiguous. We therefore recommend that, the 2010 Cyber Law should be amended to address the current issues of ICT. This amendment should include explicit definitions for the different forms of cybercrimes with severe sanctions. Banks are advised to put in place effective monitoring machineries to mitigate cybercrimes.

An analysis of the challenges in combatting money laundering within Bureaux de Change establishments in Botswana - Mokone, Philadelphia Pontsho (Journal of Money Laundering Control, 2025)
PURPOSE : Financial institutions such as Bureaux de Change are susceptible to money laundering, posing a significant risk to a nation’s financial stability and security if not properly regulated and supervised. Botswana is a member of the Financial Action Task Force (FATF), a global organisation that sets standards, promotes policies to prevent money laundering, terrorist financing and arms proliferation, all to safeguard the global financial system. Efforts have been made to incorporate FATF recommendations on money laundering into the fiscal laws of Botswana. However, some deficiencies still remain. Although there are no recorded cases of money laundering in Botswana, Bureaux de Change entities are susceptible to it as their business involves cash transactions and rapid money transactions. This paper aims to analyse the challenges faced by Bureaux de Change entities in combating money laundering in Botswana. This will be done by assessing the effectiveness of the current regulatory framework and role of the regulatory authorities in combating money laundering within Bureaux de Change entities. DESIGN/METHODOLOGY/APPROACH : This paper provides a comprehensive examination of the obstacles faced by Bureaux de Change entities in Botswana when it comes to combating money laundering. A qualitative research method and doctrinal research method are both used in this context. FINDINGS : It is hoped that policymakers and other relevant persons will adopt the recommendations provided in the paper to enhance the curbing of money laundering in Botswana. RESEARCH LIMITATIONS/IMPLICATIONS : This paper is only limited to the regulation of money laundering within the Bureaux de Change entities in Botswana and does not provide empirical research. PRACTICAL IMPLICATIONS : This paper is useful to policymakers, lawyers, law students and regulatory bodies especially in Botswana. SOCIAL IMPLICATIONS : This paper suggests changes to the Bank of Botswana (Bureaux de Change) Regulations of 2004 to improve their effectiveness, robustness and competitiveness in combating money laundering. ORIGINALITY/VALUE : This paper is original research on the challenges of combating money laundering within Bureaux de Change entities in Botswana.
Emerald Publishing Limited
Keywords: Botswana; Bureaux de Change; Cash transactions; Financial security; Financial stability; Money laundering; Risk; Supervision

A legal analysis of the application of the FATF grey-listing standards on South Africa - Mthembu, Zanele (North-West University, 2025)
The Financial Action Task Force (FATF) is a watchdog established to counter the abuse of the financial system by criminals for money laundering, the financing acts of terrorists and proliferation financing. For the FATF to achieve its mandate, it came up with a set of global standards in the form of Recommendations. The Recommendations seek to mitigate the risks of money laundering and terrorist financing and to assess whether FATF member countries are taking effective action to combat money laundering and terrorist financing. South Africa is a member of the FATF and therefore, is obliged to comply with the standards set to combat money laundering and terrorist financing and proliferation. The FATF uses assessments done through peer mutual evaluations. In other words, FATF members assess one another’s anti-money laundering and counter-terrorism financing (AML/CTF) regulatory frameworks for compliance with FATF’s standards. Following the FATF's assessment in the years 2003, 2009 and 2018, South Africa’s AML/CTF regulatory framework was found to be weak leading to greylisting in 2023. The greylisting of South Africa follows the findings of strategic deficiencies in the country’s implementation of the FATF AML/CFT standards. Greylisting by the FATF carries various economic and reputational implications for South Africa such as increased scrutiny from international partners resulting in increased compliance costs for financial institutions, an estimated reduction in South Africa’s gross domestic product (GDP) and a decrease in foreign direct investment (FDI). Since the greylisting, South Africa has embarked on a legislative and regulatory journey to address the shortcomings with a view to be taken off the greylist. This dissertation provides a detailed analysis of the FATF standards, evaluates South Africa's legislative and institutional responses in the form of the Prevention of Organised Crime Act 121 of 1998, Financial Intelligence Centre Act 38 of 2001 and the Protection of Constitutional Democracy Against Terrorist and Related Activities Act 33 of 2004, and assess their effectiveness in addressing the identified deficiencies. Recommendations are suggested to assist in fortifying South Africa’s AML/CTF regulatory framework.
Keywords: Accountable institutions; GAFI; Greylist; Money laundering; Mutual evaluation; Recommendations; Terrorism financing